1-[4-(1H-imidazol-1-yl)phenyl]ethanone monohydrate - Ibrahim, Halliru (International Union of Crystallography, 2012)
In the crystal structure of the title compound, C(11)H(10)N(2)O·H(2)O, the solvent water molecule links the organic molecules through O—H⋯O and O—H⋯N hydrogen bonds, forming chains that run diagonally across the bc face. These chains are connected to adjacent chains through weak C—H⋯O interactions, resulting in hydrogen-bonded sheets extending along the b and c axes. The sheets are connected along the a axis through π–π interactions, with centroid–centroid distances of 3.7571 (9) and 3.7231 (9) Å.